ANALYSIS OF THE FACTORS THAT DRIVE CUSTOMER WILLINGNESS TO PURCHASE AT PREMIUM PRICE OF NIKE’S PRODUCT (CASE STUDY AT NIKE’S SPORT SHOES) - Kalangie, Christian I.; Worang, Frederik G. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: the world now has facing the industry challenge where most of the company compete to create another way and fresh idea about how the product should be marketed and consumed by consumers continuously and sustainably, specially for the premium product. it takes strategy as a guideline for deploying the mission and goals to be achieved by the company. Limitations in resources and the uncertainty of the strength of the broader market competition require the right strategy in marketing. Price is something that is used as a measure or indication of the value and the benefits of consumers, and for premium product, of course it needs Premium pricing strategy, which is one of the strategies in pricing the high price level. It is done as a form of imaging that the value of the products offered are value and high quality, and it is challenging for the company since premium product treatment is quite different with regularly product, what separate it is value is the price itself. Keyword: Premium Price, Willing to pay